ANALISIS GERAK OVERHEAD LOB (FOREHAND) TERHADAP KETEPATAN LOB ATLET BULUTANGKIS USIA 11-13 TAHUN DI PB GANESHA BATU - Diana Susilowati; Mulyani Surendra; Rias Gesang Kinanti (Jurnal Sport Science, 2017)
Abstract: Hurdling is one of a number run, however, the use of the net as obstacles that must be traversed by the runner without having to lose the running speed as it passes through the goal or obstacle. The purpose of this research is to find out the influence of exercise variations ladder exercise to increased speed of 200-metres hurdling on Sport Science Department Student the class of 2013. Ths study has shown the experimental group p = 0.000 <0.05 while the control group 0.000 <0.05, which means that Ho refused. So between these results indicate an increase in the speed of the second group 200 meter hurdles, but seen from the figures the fastest time of the experimental group had an average time better than the control group. This is because of differences in training load in both groups.Keyword: Hurdling, speed, ladder exercise variations